Multiscale-based bioproduct design with vegetable extracts of promising amazonian species (2018)
"Using innovative bioprospection techniques not only allows to find biological species that could be used as a primary source for obtaining new products, but also to develop those new products and to design their industrial production. This project proposes a multiscale approach as a rational bioprospection way to design emulsions constituted mainly by natural ingredients. The oil phase was obtained from some fruits of Arecaceae species from Colombiaþs amazon region, while the evaluated surfactants were two outer membrane proteins (OmpA and OmpN) obtained from Escherichia coli culture. This approach allowed us to understand how properties at different scales relate to each other, to evaluate the effect of process and product formulation on the emulsion performance, and finally to gauge the surfactant effectiveness. Emulsion quality is related to its stability that could be evaluated considering its properties at the macroscopic, microscopic and molecular scales. For this reason, our work started with a complete molecular characterization of the raw materials as basis to understand their behavior in the formulated emulsions. First, each oil product composition was analyzed by determining the concentration of the main components. As second step, the biosurfactant molecular behavior, at water - triglycerides interfaces, was evaluated in silico through molecular dynamics (MD), and in vitro. Thus, the MD results rationalized the measured experimental evidence. Finally, we implemented a multiscale approach to design emulsions from a knowledge of the composition of the oil phase and its interaction with the surfactant. Properties of formulated emulsions were analyzed from molecular, microscopic and macroscopic scales."--Tomado del Formato de Documento de Grado.